WATERFALLS: FORMS, DISTRIBUTION, PROCESSES AND RATES OF RECESSION - Goudie, Andrew S. (Quaestiones Geographicae, 2020)
A waterfall is a very steep (commonly nearly vertical) fall of some magnitude in a river course. Waterfalls are widespread fluvial landforms that have been described from many parts of the world. Thirty-eight World Heritage Properties include waterfalls in their designation. In addition, some waterfalls are actual or potential geomorphosites. Waterfalls occur in almost all climatic environments, though they are particularly common in formerly glaciated areas. They occur on a huge diversity of rock types, although in general, they do not form persistent or large falls on soft or unconsolidated rocks. Waterfalls also occur in a wide range of geomorphological settings: glaciated areas, areas of active tectonism, areas of sea-cliff retreat and sea-level change, great escarpments on passive margins, basins with river capture, rifted and faulted areas and areas that have been subjected to megaflooding. Multiple processes account for waterfall retreat and varying rates of recession. Although the greatest interest has been in rates of waterfall recession, there are examples of waterfalls that prograde as a result of tufa deposition.